Effectiveness of a web-based psycho-education intervention program on depression and anxiety among adults in Selangor, Malaysia - Kader Maideen, Siti Fatimah (2016)
Mental disorders are a major global public health problem. Among all the mental health disorders, depression and anxiety are the most common. The burden and disability resulting from mental disorders is significant, and yet mental disorders are largely left untreated and patients do not receive professional care. This research has been conducted with the aim of determining the prevalence and predictors of depression and anxiety among adults in Selangor, and how a brief psycho-education program can address this problem. A cross sectional study was conducted in three districts of Selangor, from 11th June to 30th December 2012. The sampling frame was obtained from the Department of Statistics Malaysia (DOS) in May 2012, using the National Population and Housing Census 2010. Adults aged 18 years and above who were Malaysian citizens and living in the selected living quarters were approached to participate in the study and were requested to complete a set of questionnaires. A total of 1,556 out of 2,512 participants participated in this study, giving an overall study response rate of 61.90%. Patient Health Questionnaire 9 (PHQ-9) was used to determine the presence of depression, whereas the Generalized Anxiety Disorder 7 (GAD 7) was used to detect anxiety. The prevalence of depression and anxiety in this study was 10.3% and 8.2%, respectively. Based on the multivariate logistic regression analysis, the predictors of depression were presence of anxiety, serious problems at work, unhappy relationship with children, high perceived stress, domestic violence, unhappy relationship with spouse, low self-esteem, unhappy relationship with family, serious financial constraint and the presence of chronic diseases. Based on the additional multivariate logistic regression analysis whereby all the covariates were considered except high stress, anxiety, and low self-esteem, the additional predictors of depression were serious marital problem, non-organizational religious activity and intrinsic religiosity. The predictors of anxiety were depression, serious problems at work, domestic violence and high perceived stress. Based on the additional multivariate logistic regression analysis after removing stress, depression and selfesteem, the additional predictors of anxiety were cancer, unhappy relationship with family, non-organizational religious activity and intrinsic religiosity. A brief web-based psycho-education intervention program was developed based on these predictors. The intervention program consisted of four sessions, with each session accessed on a weekly basis. A two-arm randomized controlled trial of a single blind study was conducted to compare four weeks of the web-based psycho-education intervention program versus a wait list control group. Participants who have participated in the first phase of this study and who were still living in Selangor; having access to computer and internet connection and are internet literate were invited to participate in the study. A list of eligible participants who consented to participate in the study was numbered. By using a random number table, the participants were randomly allocated to either the intervention or the control group. A total of 119 participants were included in Phase 2 of study. All the participants completed the online questionnaires at week 1, week 5 and week 12. Participants in the intervention group were allowed to view the full content on the website and use the program as frequently and for as long as they wanted. The primary outcomes of this study were the change in depressive and anxiety score, whereas the secondary outcome was the change in the mental health literacy score. The baseline scores of outcome measures showed no significant differences between the intervention and control group. The mixed between-within subject ANOVA was used to compare mean difference of the psycho-education intervention program between the intervention and control groups at baseline, post-test (week 5) and 2-months of follow up (week 12). Results revealed a significant difference in the mental health literacy between the intervention and the control group. No significant difference was found in the depression and anxiety scores. The psycho-education intervention was found to be effective in increasing the mental health literacy of the participants.